Using Dramatization to Teach Starling Forces in the Microcirculation to First-Year Medical Students - Brian William Connor; Helena Carvalho (Association of American Medical Colleges, 2019)
Introduction The clinical importance, prevalence, and multiple etiologies of tissue edema make it a critical part of medical education. Given the multiple physiological parameters that must be simultaneously considered to determine fluid movement, it is important that a deeper understanding of the microcirculation and fluid shifts is achieved in preclinical education. Methods We describe an innovative teaching methodology using dramatization to interactively teach Starling forces to first-year medical students. Prior to the dramatization, students were given an introduction to Starling forces. They also completed a brief knowledge quiz on the topic before and after the activity. The classroom walls were marked with signs representing the intravascular space, extravascular or interstitium, and lymphatics compartments. Students were invited to act out or mimic the fluid shifts within capillaries as the values for hydrostatic and colloid osmotic pressures for the intravascular and interstitial spaces were presented. The goal was for each student to decide which compartment he/she would move to as fluid according to Starling force values and/or clinical scenarios. Results A significant improvement between pre- and postactivity quiz performance (45.4% ± 25.1% and 77.5% ± 14.1%, respectively) was observed (n = 26, p < .001, t test). In a postactivity survey, 85% of students reported the activity to be an effective way of learning. Discussion Our data indicate that this dramatization approach is effective in complementing passive learning in traditional lectures. Furthermore, this type of dynamic activity brings joy to the classroom and breaks the monotony of lecturing.